2002
DOI: 10.1002/ajmg.10464
|View full text |Cite
|
Sign up to set email alerts
|

Personal experiences of cystic fibrosis (CF) carrier couples prospectively identified in CF families

Abstract: This qualitative study explores the experiences of cystic fibrosis (CF) carrier couples, prospectively identified in CF families, and the impact of the resulting genetic risk on reproductive behavior. Of the 12 couples identified until 1997, seven couples participated in semistructured interviews and two couples filled in a questionnaire, two to eight years after receipt of the test-results. After receiving the results, most couples reported that they were shocked, because they did not expect to both be carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 18 publications
(13 reference statements)
4
34
0
Order By: Relevance
“…Couples elected to terminate the pregnancy in 106 cases (95%) [64]. Smaller studies found similar results [65,66,67,68,69,70,71,72,73]. …”
Section: Resultssupporting
confidence: 53%
“…Couples elected to terminate the pregnancy in 106 cases (95%) [64]. Smaller studies found similar results [65,66,67,68,69,70,71,72,73]. …”
Section: Resultssupporting
confidence: 53%
“…Disclosure of risk to extended family members was not well communicated by the parents in our study but disclosure to the immediate family (parents, siblings) being more common. The difficulty with disclosure and underused cascade testing has been seen in other studies where parents felt they were under obligation to inform family 14–16 …”
Section: Discussionmentioning
confidence: 83%
“…Impact on reproduction has been highlighted as a key issue when learning about one's carrier status in other studies focusing on single-gene disorders, [24][25][26][27] and therefore this result is not surprising. These observations emphasize the need for expert pre-test counseling before screening and add to concerns that implementing NIPD may erode informed choice.…”
Section: Discussionmentioning
confidence: 96%